Development of a BCG challenge model for the testing of vaccine candidates against tuberculosis in cattle - Villarreal-Ramos, B; Berg, S; Chamberlain, L; Mcshane, H; Hewinson, R; Clifford, D; Vordermeier, M (Elsevier, 2014)
Vaccination is being considered as part of a sustainable strategy for the control of bovine tuberculosis (BTB) in the UK. The live attenuated Mycobacterium bovis bacillus Calmette-Guerin (BCG) has been used experimentally to vaccinate cattle against BTB. However, BCG confers partial protection against BTB and therefore, there is a need to develop improved vaccines. BTB vaccine efficacy experiments require the use of biosafety level 3 facilities which are expensive to maintain, generally oversubscribed and represent a bottle neck for the testing of vaccine candidates. One indicator of the induction of protective responses would be the ability of the host's immune response to control/kill mycobacteria. In this work we have evaluated an intranodal BCG challenge for the selection of vaccine candidates at biosafety level 2 which are capable of inducing mycobactericidal responses. To our knowledge, this is the first such report. Whilst BCG only confers partial protection, it is still the standard against which other vaccines are judged. Therefore we tested the BCG intranodal challenge in BCG (Danish strain) vaccinated cattle and showed that vaccinated cattle had lower BCG cfu counts than naïve cattle at 14 and 21 days after intranodal challenge with BCG (Tokyo strain). This model could help prioritize competing TB vaccine candidates and exploration of primary and secondary immune responses to mycobacteria.